A Novel Curcumin-Galactomannoside Complex Delivery System Improves Hepatic Function Markers in Chronic Alcoholics: A Double-Blinded, randomized, Placebo-Controlled Study. (23rd September 2018) - T. Krishnareddy, Naveen; Thomas, Jestin V.; Nair, Saritha S.; N. Mulakal, Johannah; Maliakel, Balu P.; Krishnakumar, I. M.
Abstract : Considering the recent interest in free (unconjugated) curcuminoids delivery, the present study investigated the efficacy of a novel food-grade free-curcuminoids delivery system (curcumin-galactomannoside complex; CGM) in improving the hepatic function markers (inflammation and oxidative stress) in chronic alcoholics. The double-blinded, placebo-controlled study randomized 48 subjects with elevated serum transaminases and gamma-glutamyl transferase (GGT) levels, who were allocated to two groups (n=24) and to receive either placebo or CGM at (250 mg × 2)/day for 8 weeks. While liver function markers (transaminases and GGT) in the placebo group showed an increase (~ 9.5%), CGM group indicated a significant decrease in transaminases (31%) and GGT (29%) from the baseline levels. The beneficial effect of CGM was also clear from the significant increase (p <0.001) in endogenous antioxidants (GSH, SOD, and GPx) and decrease in inflammatory markers (IL-6 and CRP) levels (p <0.001) as compared to both the baseline and placebo group. To summarize, the nutritional intervention of CGM-curcumin was found to offer a significant hepatoprotective effect to attenuate the alcohol induced alterations to hepatic function markers. The Indian Medical Council and Drug Controller General of India approved Clinical Trial Registry No. CTRI/2018/03/012385 .